Mucosal CD8 T Cell Responses Are Shaped by Batf3-DC After Foodborne Listeria monocytogenes Infection - Imperato, Jessica Nancy; Xu, Daqi; Romagnoli, Pablo A.; Qiu, Zhijuan; Perez, Pedro; Khairallah, Camille; Pham, Quynh-Mai; Andrusaite, Anna; Bravo-Blas, Alberto; Milling, Simon W. F.; Lefrancois, Leo; Khanna, Kamal M.; et al. (Frontiers in Immunology, 2020)
While immune responses have been rigorously examined after intravenous Listeria monocytogenes (Lm) infection, less is understood about its dissemination from the intestines or the induction of adaptive immunity after more physiologic models of foodborne infection. Consequently, this study focused on early events in the intestinal mucosa and draining mesenteric lymph nodes (MLN) using foodborne infection of mice with Lm modified to invade murine intestinal epithelium (InlAM Lm). InlAM Lm trafficked intracellularly from the intestines to the MLN and were associated with Batf3-independent dendritic cells (DC) in the lymphatics. Consistent with this, InlAM Lm initially disseminated from the gut to the MLN normally in Batf3-/- mice. Activated migratory DC accumulated in the MLN by 3 days post-infection and surrounded foci of InlAM Lm. At this time Batf3-/- mice displayed reduced InlAM Lm burdens, implicating cDC1 in maximal bacterial accumulation in the MLN. Batf3-/- mice also exhibited profound defects in the induction and gut-homing of InlAM Lm-specific effector CD8 T cells. Restoration of pathogen burden did not rescue antigen-specific CD8 T cell responses in Batf3-/- mice, indicating a critical role for Batf3 in generating anti-InlAM Lm immunity following foodborne infection. Collectively, these data suggest that DC play diverse, dynamic roles in the early events following foodborne InlAM Lm infection and in driving the establishment of intestinal Lm-specific effector T cells.